2023
DOI: 10.1111/nph.19093
|View full text |Cite
|
Sign up to set email alerts
|

Climbing mechanisms and the diversification of neotropical climbing plants across time and space

Patrícia Sperotto,
Nádia Roque,
Pedro Acevedo‐Rodríguez
et al.

Abstract: Summary Climbers germinate on the ground but need external support to sustain their stems, which are maintained attached to supports through modified organs, that is, climbing mechanisms. Specialized climbing mechanisms have been linked to higher diversification rates. Also, different mechanisms may have different support diameter restrictions, which might influence climbers' spatial distribution. We test these assumptions by linking climbing mechanisms to the spatiotemporal diversification of neotropical clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Interestingly, Sperotto et al . (2023) do not find that climbing growth forms influenced evolutionary diversification rates as inferred from phylogenetic trees, at least not in Neotropical climbers. Discrepancies in diversity across Neotropical angiosperm lineages are therefore probably not related to specific climbing mechanisms.…”
Section: The Drivers Of Plant Diversity and Life Formsmentioning
confidence: 87%
“…Interestingly, Sperotto et al . (2023) do not find that climbing growth forms influenced evolutionary diversification rates as inferred from phylogenetic trees, at least not in Neotropical climbers. Discrepancies in diversity across Neotropical angiosperm lineages are therefore probably not related to specific climbing mechanisms.…”
Section: The Drivers Of Plant Diversity and Life Formsmentioning
confidence: 87%
“…We found that phylogenetic relatedness plays an even more important role than climate and paleoclimate in explaining the distribution of active and passive climbing mechanisms. The stronger effect of phylogeny on the representation of active and passive climbing species may be related to the limited number of lineages that undergo local radiations, rather than by the convergence of climbing mechanisms in regions with similar climates (Sperotto et al, 2020(Sperotto et al, , 2023. For instance, when species concentrated in a given climate or region are represented by a few families, this pattern might be a consequence of shared ancestry rather than independent events of the evolution of that climbing mechanism (Sperotto et al, 2023).…”
Section: Environmental Variable Predictors and Distribution Of Climbi...mentioning
confidence: 99%